(untitled) (Archaeologia Adriatica, 2026)
Ankylosing spondylitis is a progressive, non-infectious and chronic inflammatory rheumatic disease characterised by calcification of connective tissue, most commonly in the sacroiliac, vertebral and costovertebral joints. In the late stages of the disease, the spine assumes the so-called bamboo-spine appearance. Sufferers face chronic pain, deformities and reduced mobility on a daily basis. Late stages of the disease lead to respiratory insufficiency, loss of neurological functions and even death. This study deals with the osteological remains of a young man from Grave 313 at the early modern archaeological site of Žumberak – St Nicholas the Bishop. Osteological changes observed on the bones are consistent with those characteristic of ankylosing spondylitis. The presence of these changes and the degree of disease progression indicate a very rapid and aggressive course. The man had a markedly pronounced kyphosis in the thoracic spine and lordosis in the cervical spine. Given the narrowing of the intervertebral space between the cervical vertebrae, which leads to compression of the spinal cord, ankylosing spondylitis is the most likely cause of death. Differential diagnoses ruled out diffuse idiopathic skeletal hyperostosis, reactive arthritis, melorheostosis, rheumatoid arthritis and psoriatic arthritis. This is the first recorded case of ankylosing spondylitis from continental Croatia during the early modern era.